Effectiveness of Problem Based Learning Supported by Interactive Multimedia and Digital Simulation on Critical Thinking Skills - Dian Hardiyanti; Kardoyo (Journal of Economic Education, 2026)
This study aims to determine the effectiveness of the multimedia-assisted Problem Based Learning model and digital simulation on students' critical thinking skills. This is a quantitative quasi-experimental study, with a pretest-posttest non-equivalent group design. The population consisted of 431 tenth-grade students at SMA N 3 Semarang, and the sample consisted of 72 students. The sampling technique used was purposive sampling. Data collection methods included pretest and posttest, student questionnaires that had been tested for validity using SPSS Version 31, and observation sheets. Data analysis methods included descriptive statistical analysis, independent sample t-test, and N-Gain test. The results showed that the use of PBL assisted by digital simulation was more effective than the use of PBL assisted by interactive multimedia. This was seen from the average posttest results in the experimental class, which was 79.03, while in the control class it was 74.22. Then, the N-Gain test score for the control class was 49.94 or 50%, which was categorized as ineffective. Meanwhile, the N-Gain of the experimental class was 61.50 or 62%, which is classified as moderately effective. Researchers are expected to further expand the learning model used according to needs and conditions and select learning media that are interesting but also suitable for learning activities.